Entrepreneurship education from the perspective of law and Islam - Fadhlurrahman, Fadhlurrahman; Ichsan, Yazida (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
Entrepreneurship education is a concept that must be socialized on a large scale. This is stated in Presidential Regulation 5 of 2010 concerning the National Medium-Term Development Plan (RPJMN). The study in this article covers the concept of entrepreneurship education in general, and the practices carried out by the famous Islamic figure, the Prophet Muhammad, and his companions. It will guide entrepreneurs to stick to the values of previous Muslim entrepreneurs. This article aims to explain the concept of entrepreneurship education and what has been done by the Prophet Muhammad and his companions. The methodology used in this research is library research. The approach used is historical and content analysis toproduce a broad and contextual picture. The stages of this method are collecting primary sources that are thematic and then reinforced with secondary sources and contextualizing. The findings in this paper about the values of entrepreneurship education in general at the Ministry of National Education are Independent, Creative, Dare to Take Risks, Action Oriented, Leadership, Hard Work, Honesty, Discipline, Innovativeness, Responsibility, Cooperation, Never Giving Up, tenacious, Commitment, Realistic, Curiosity, Communicative, Strong motivation to succeed. The Quraysh had practiced the spirit of entrepreneurship education, as did Hasyim bin 'Abdul Manaf, which the Prophet then practiced from an early age to adulthood, and his closest friends who became successful entrepreneurs, such as Abdurrahman bin Auf.